Validation into Portuguese of the Maugerl Cardiac prevention-Questionnaire (MICRO-Q) Validação para o Português do Maugerl CaRdiac preventiOn-Questionnaire (MICRO-Q) - Ghisi G.L.D.M.* (2010)
Background: The Maugerl CaRdiac preventiOn-Questionnaire (MICRO-Q) is a validated specific tool used to assess the knowledge of the patient with coronary disease on aspects related to the secondary prevention of coronary artery disease (CAD). Objective: To translate, adapt and validate the MICRO-Q to Brazilian Portuguese. Methods: Two initial independent translations were carried out into Brazilian Portuguese. After their comparison, the reverse translation was carried out, which was reviewed by a committee and generated the final version that was tested in a pilot study. The tool was applied to 212 coronary patients, with a mean age of 60 to 71 years (standard deviation = 9.4; range: 35-86) that participated in cardiac rehabilitation programs. The internal consistency was verified by Cronbach's Alpha Coefficient, correlation through Spearman's Rho and the validity of the construct was verified through exploratory factorial analysis. The means were analyzed by comparing the scales of the correct questions in relation to variables such as age, sex, associate comorbidities, degree of schooling, family income, among others. Results: The Brazilian version of the MICRO-Q has 25 questions. The reliability of this version presented a Cronbach's Alpha Coefficient of 0.64 and a Spearman's Rho of the correct answers of 0.65. The factorial analysis showed 6 factors related to the domains of knowledge of the questionnaire. The analysis of the population characteristics regarding the scales of the correct questions presented significant differences only in relation to monthly family income and degree of schooling. Conclusion: The approved Brazilian version of the MICRO-Q presents adequate validity and reliability for its use in future studies.